CUTE Mote, a customizable and trustable end-device for the Internet of things - Gomes, Tiago Manuel Ribeiro (2017)
The ubiquitous connectivity of the low-end devices in the Internet of Things (IoT) brings new challenges over the traditional wireless sensor networks' architectures. Such challenges require not only security and privacy-related features, but also solutions to handle the ever-growing amount of data transferred over the network. However, performing such tasks on resource constrained devices is not straightforward. The need for energy-efficient devices, while preserving their performance and security capabilities, requires new solutions at the architectural level of the wireless device. This paper proposes a heterogeneous architecture that targets low-end and resource constrained IoT devices, combining a hardcore microcontroller unit (MCU) and a reconfigurable computing unit (RCU) with an IEEE 802.15.4 radio transceiver. The MCU hosts an embedded operating system with an IoT-enabled network stack, and exploits the available field-programmable gate array technology to implement the RCU and to deploy customized sensing- and network-related accelerators, offloading heavy, and/or complex software tasks to dedicated hardware blocks. The customizable and trustable end-device mote was implemented using the proposed architecture and the achieved results demonstrates the benefits, both in terms of performance and energy, of accelerating network-related tasks in always-connected resource constrained IoT devices.